Innovative application of contemporary management methods in a knowledge-based economy – interdisciplinarity in science - Ejdys, Joanna; Ustinovičius, Leonas; Stankevičienė, Jelena (Journal of Business Economics and Management, 2014)
Interdisciplinarity, which is a part of the research paradigm in all fields of science, constitutes a real challenge in research. It manifests itself particularly in the diversity of the undertaken research topics, in the variety of the adopted research approaches (theoretical, methodological, normative, empirical-descriptive), and in the flexibility and the ability to see both the scientific problems as well as the economic and social needs. The ability to cross the boundaries between the fields of technical and social sciences, to identify problems and to seek solutions at the frontiers of scientific disciplines, the eagerness to work in research teams diverse in terms of competence, age and skills, creating conditions for both the personal development and that of individual team members, breaking the stereotypical ways of thinking in the process of solving problems and anticipating future events are all features of an academic culture nurtured by Professor Joanicjusz Nazarko. The paper highlights the research of Professor Joanicjusz Nazarko, presents a review of his extensive scientific work and lists some of his publications.